2022
DOI: 10.3389/fimmu.2022.1018567
|View full text |Cite
|
Sign up to set email alerts
|

A metagenome-wide association study of the gut microbiota in recurrent aphthous ulcer and regulation by thalidomide

Abstract: Recurrent aphthous ulcer (RAU), one of the most common diseases in humans, has an unknown etiology and is difficult to treat. Thalidomide is an important immunomodulatory and antitumor drug and its effects on the gut microbiota still remain unclear. We conducted a metagenomic sequencing study of fecal samples from a cohort of individuals with RAU, performed biochemical assays of cytokines, immunoglobulins and antimicrobial peptides in serum and saliva, and investigated the regulation effects of thalidomide adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Thalidomide could upregulate the abundance of Lactobacillus and ameliorate recurrent aphthous ulcers. 31 Symbiotic treatment containing fructooligosaccharide, Lactobacillus , and Bifidobacterium was able to reduce pain in recurrent aphthous stomatitis patients. 32 Besides, Oscillospira and Phascolarctobacterium are also recognized as probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide could upregulate the abundance of Lactobacillus and ameliorate recurrent aphthous ulcers. 31 Symbiotic treatment containing fructooligosaccharide, Lactobacillus , and Bifidobacterium was able to reduce pain in recurrent aphthous stomatitis patients. 32 Besides, Oscillospira and Phascolarctobacterium are also recognized as probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota is increasingly recognized as a key factor in human health (Gilbert et al, 2018). A large number of studies have shown that changes in gut flora are closely linked to the development of type 2 diabetes (Bajzer and Seeley, 2006; Wang et al, 2022; Zhang et al, 2010). Some studies have shown that polysaccharides exert hypoglycemic and hypolipidemic activities mainly by reducing the abundance of harmful bacteria and increasing the abundance of beneficial bacteria (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%